Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan E-LKPD untuk Meningkatkan Hasil Belajar Ekonomi Siswa SMA Negeri 1 Dawan - Ni Kadek Wina Febiyanti; Luh Indrayani (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning learning model assisted by E-LKPD to improve the learning outcomes of students in economics at SMA Negeri 1 Dawan. The type of research used is a quasi- experimental study